If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -17 = 520 Reorder the terms: -17 + X = 520 Solving -17 + X = 520 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + X = 520 + 17 Combine like terms: -17 + 17 = 0 0 + X = 520 + 17 X = 520 + 17 Combine like terms: 520 + 17 = 537 X = 537 Simplifying X = 537
| -4(6y-6)-y=-2(y-4) | | x(x)-5x-3=2 | | 14-18x=0 | | 5x+6=-48+-4x | | 2x^2-25x-72= | | 26x+17=5(5x+1) | | 9x^2+8x-9=8x | | 4x-4-8y+8-5y= | | 2x+3y=5x-2y-4y | | 15+5c-2=29 | | 38+[23-(13+10)]= | | 5x+6=48-4x | | y*y=36 | | 1000x=(1000x-1x) | | 3m+g=2k | | 0.4y+0.7=0.2-0.1y | | -2k-3=19 | | 6x-5+1=-13 | | -7=-8 | | 198=90+x+5x | | 3x-([-5x]-11)=(-197) | | 5y+8=38 | | S=2(pie)rh | | 7(a+1)-3a=5+4(a-1)2 | | 2x+y=(-9) | | 66.6(6j+9)=3j+7 | | 7x=-1.60 | | -2(z+4)=-(z-5) | | 6(3n+4)=7(8n+4)+7 | | 3a+12=343 | | x-8-2(x+1)=-10 | | -2(3t-4)+4t=8t-9 |